Pengaruh Independensi, Kompetensi, Akuntabilitas, Pengalaman Dan Motivasi Terhadap Kualitas Audit Pada Aparat Inspektorat Dalam Pengawasan Keuangan Daerah(Studi Empiris pada Inspektorat Pemerintah Kabupaten Sukoharjo) - Marganingsih, Marganingsih; , Drs. Eko Sugiyanto, M.Si (2016)
This study aimed to analyze the influence of the independence competence, accountability, experience and motivation of the auditors on audit quality in Apparatus Regional Inspectorate Financial Supervisory Sukoharjo regency government. n this study are Pegawai Negeri Sipil (PNS) working in the Inspectorate of Government of Sukoharjo district. The sampling method with a purposive sampling in accordance with predetermined criteria. This research data obtained from the questionnaire (primary). This research uses a quantitative approach and using a type of causality. The analysis used is multiple linear regression analysis with f test, t test and the coefficient of determination. The results showed simultaneous variable independence, competence, accountability, experience, and motivation effect on audit quality. The partial results of the study as follows: (1) Independence does not affect the quality of the audit, the result is evidenced by the significant value greater than 5% (0.113> 0.05), so that H1 is rejected. (2) Competence effect on audit quality, is evidenced by the results of significant value less than 5% (0.004 <0.05), so that H2 is accepted. (3) Accountability does not affect the quality of the audit, the result is evidenced by the significant value greater than 5% (0.135> 0.05), so that the H3 is rejected. (4) Pengalamaan effect on audit quality, is evidenced by the results of significant value less than 5% (0.031 <0.05), so H4 is accepted. (5) The motivation does not affect the quality of the audit, the result is evidenced by the significant value greater than 5% (0.135> 0.05). H5 is rejected.